Baker's biographical dictionary of musicians. - Slonimsky, Nicolas, 1894-; Kuhn, Laura Diane (New York : Schirmer Books, 2001)
"Nicolas Slonimsky's venerable single-volume reference is now a six-volume set, with better page layout and typeface, and a subject range outside its traditional concentration on classical music. Under new editorship since Slonimsky's death in 1995, coverage has expanded to over 1,000 new entries on classical music and over 2,000 new entries on jazz and popular music. Nice features include reprints of Slonimsky's witty introductions to earlier editions and indexes for genre, nationality, and women composers and musicians."--"Outstanding Reference Sources," American Libraries, May 2002.
v. 1. Aalt-Cone -- v. 2. Conf-Gysi -- v. 3. Haar-Levi -- v. 4. Levy-Pisa -- v. 5. Pisc-Stra -- v. 6. Stre-Zyli. Indexes (genre, nationality, women)
Previous ed.: 1992.
Includes bibliographical references and discographies.
English
Keywords: Music -- Bio-bibliography -- Dictionaries